2009
DOI: 10.1063/1.3259405
|View full text |Cite
|
Sign up to set email alerts
|

Electron paramagnetic resonance characterization of defects in monoclinic HfO2 and ZrO2 powders

Abstract: Electron paramagnetic resonance (EPR) measurements have been made at X-band and room temperature on monoclinic HfO2 and ZrO2 powders from several suppliers. They reveal the presence of eight main paramagnetic centers H1, H2, H3, H4, and Z1, Z2, Z3, and Z4. H1 and Z1 are analogous as H4 and Z4 and H2 and Z2 are similar as H3 and Z3. H1 and Z1 have axial symmetry with g∥<g⊥<ge, where ge is the free electron g value. H1 is found in all, and Z1 in all but one, of the samples in their as-received stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 84 publications
1
10
1
Order By: Relevance
“…4,6,11,13,[15][16][17][18] There has been no fully accepted chemical identification of the oxygen vacancy in HfO 2 by, say, electron spin resonance (ESR). [19][20][21] This situation differs from the oxygen vacancy in TiO 2 22 and contrasts strongly with the vast literature on the paramagnetic E 0 and P b centers in SiO 2 . 23,24 In this paper, we explain the problems with the symmetry assignment of the oxygen vacancy in HfO 2 in previous calculations and present a calculation of the ESR signature of the O vacancy using hybrid density functional methods, to help aid this identification.…”
contrasting
confidence: 40%
See 1 more Smart Citation
“…4,6,11,13,[15][16][17][18] There has been no fully accepted chemical identification of the oxygen vacancy in HfO 2 by, say, electron spin resonance (ESR). [19][20][21] This situation differs from the oxygen vacancy in TiO 2 22 and contrasts strongly with the vast literature on the paramagnetic E 0 and P b centers in SiO 2 . 23,24 In this paper, we explain the problems with the symmetry assignment of the oxygen vacancy in HfO 2 in previous calculations and present a calculation of the ESR signature of the O vacancy using hybrid density functional methods, to help aid this identification.…”
contrasting
confidence: 40%
“…18 In ESR, Kang et al 19 have observed various paramagnetic defects such as the peroxyl radical in atomic layer deposited (ALD) HfO 2 . Wright and Barklie 20 observed a number of low symmetry defects in HfO 2 powders and thin films that they associated with under-coordinated Hf 3þ sites. Stesmans 21 observed the P b center in HfO 2 on Si, but this was associated with the SiO 2 interlayer not the HfO 2 itself.…”
mentioning
confidence: 99%
“…The trap for the holes is not clear; however the valence band top is formed from the oxygen 2p states [23] and theoretical calculation and some experiments showed the holes localized on oxygen [19,24,25]. Since the STE was observed [6] the selftrapped hole could also exist and a configuration similar to the self-trapped hole localized at some defect could be a hole center participating in non-radiative recombination.…”
Section: Resultsmentioning
confidence: 92%
“…For the 400 K irradiation, the V 0 defect appears to be the dominant defect. For the 160 K irradiation, it is not quite so clear, with both the V 2À and V À defects producing similar distortions to the lattice; however, it suggests that these two defects may be the dominant defects at 160 K. Electron paramagnetic resonance experiments [17] performed on c-ray-irradiated monoclinic ZrO 2 has shown that the V À defect is the most likely to exist, leading to the possibility that this is the most dominant defect at 160 K. This cannot be categorically proven, however, as the difference in the crystal structures (monoclinic phase versus cubic phase) may lead to different charge states being dominant.…”
mentioning
confidence: 99%
“…To date, most research has focused on radiation processes (primarily heavy ion irradiation) in either partially-or fully stabilized zirconia as single crystals or with micron-sized grains, or on nanograined ZrO 2 that are either embedded in a foreign matrix or as free-standing particles [15][16][17]. The work presented here examines the effect of heavy ion irradiation on NSZ with a view to understanding the defect production, saturation and evolution of oxygen vacancies, and how this impacts the unit cell structure.…”
mentioning
confidence: 99%